2022
DOI: 10.3390/nu14214533
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Panel of Olive Polyphenols: Mechanisms of Action, Anti-Demyelination, and Anti-Stroke Properties

Abstract: Neurological diseases such as stroke and multiple sclerosis are associated with high morbidity and mortality, long-term disability, and social and economic burden. Therefore, they represent a major challenge for medical treatment. Numerous evidences support the beneficial effects of polyphenols from olive trees, which can alleviate or even prevent demyelination, neurodegeneration, cerebrovascular diseases, and stroke. Polyphenols from olive oils, especially extra virgin olive oil, olive leaves, olive leaf extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 182 publications
1
5
0
Order By: Relevance
“…Regarding its chemical properties that allow an easy formulation free of toxicity, HT has been highly regarded as a prime food supplement by the nutraceutical and food industries and so it is of key importance to potentiate the extraction of this phenolic compound from the olive leaf [ 61 ]. Concerning the premium choice, the O. europaea Madural leaf extract presents as a worthy nutraceutical due to its HT levels, confirming the invaluable multidimensional properties of olive leaves as a low-cost source of high-added-value phenolic compounds, as determined by other authors [ 30 , 31 , 51 , 99 , 103 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Regarding its chemical properties that allow an easy formulation free of toxicity, HT has been highly regarded as a prime food supplement by the nutraceutical and food industries and so it is of key importance to potentiate the extraction of this phenolic compound from the olive leaf [ 61 ]. Concerning the premium choice, the O. europaea Madural leaf extract presents as a worthy nutraceutical due to its HT levels, confirming the invaluable multidimensional properties of olive leaves as a low-cost source of high-added-value phenolic compounds, as determined by other authors [ 30 , 31 , 51 , 99 , 103 ].…”
Section: Discussionsupporting
confidence: 69%
“…Several studies report that polyphenols derived from the olive tree are implicated in the relief and prevention of bioprocesses, such as through neurodegenerative, anti-hypertensive, and cardioprotective effects, whilst exhibiting anti-thrombotic, anti-inflammatory, antioxidant, anticancer, antimicrobial, and immune-protective properties [ 50 , 51 ]. The TPCs of the studied extracts were found to exhibit the following waning order: O. europaea Verdeal (59.30 ± 4.30 mgGAE/g sample) > Madural (48.90 ± 2.40 mgGAE/g sample) > Cobrançosa (37.90 ± 4.20 mgGAE/g sample) ( Table 2 ), which are inferior to the values found for the same cultivars harvested from another geographical region in differential cultivation conditions, where O. europaea Cobrançosa (3.37 ± 0.25 mgGAE/g sample) > Verdeal (2.47 ± 0.2 mgGAE/g sample) > Madural (2.31 ± 0.22 mgGAE/g sample) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olive tree polyphenols showed evidence of relieving or even preventing demyelination, neurodegeneration, antihypertensive and cardioprotective effects, while demonstrating anti-inflammation, antioxidant, antimicrobial and immune protective, hypocholesterolemic, hypoglycemic, anti-thrombotic, and anti-cancer properties [ 32 , 45 ]. In this study, the leaf sprouts of all the three cultivars were showed to be richer in total phenol content (TPC) compared to the respective elementary leaf sample ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main polyphenols in EVOO, OleA and its main metabolite, HT, are well studied and can be easily administered through food or in other formulations and do not present adverse reactions in humans. In particular, OleA and HT exert their neuroprotective effects by their ability to cross the blood–brain barrier (BBB) [ 38 , 39 , 40 ]; indeed, the aglycone form can cross membranes by a passive diffusion [ 38 ]. This peculiarity makes EVOO polyphenols potential nutraceutical tools and promises the realistic use of these active principles in the treatment of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%